Konsep Pendidikan Akhlak Anak Perspektif Imam Al Ghazali - Eko Setiawan (Jurnal Kependidikan, 2017)
Imam Al Ghazali is a figure with a unique and revolutionary style of thinking. He also contributed a lot of thought about moral education. Family environment is very dominant in fostering moral education and moral education should start from the family because little children spend more time in the family environment than outside the home. To form a noble character, should the child's moral planting done early on as a foundation to live his life in the future. This paper aims to describe how the concept of moral education of children according to Imam Al Ghazali.